Review on Acute Cardio-Cerebral Infarction: a Case Report - Teddy Arnold Sihite; Michi Astuti Rehmenda Mario Sitepu; Cut Azlina Effendi (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To describe a case of a Cardio-Cerebral Infarction (CCI) male patient presented with a history of chest pain recognized using electrocardiography, brain computed tomography, and Percutaneous Coronary Intervention (PCI).Methods: A 69 years old man came with history of chest pain since 13 hours before to the emergency room. Electrocardiography, brain computed tomography, and PCI were performed, leading to the diagnosis of CCI.Results: The electrocardiography showed ST Elevation in Antero-lateral, atrial fibrillation and left-sided hemipharesis, which occurred on the second day. Brain computed tomography demonstrated acute infarct stroke, while the Percutaneous Coronary Intervention (PCI) showed one vessel disease with severe stenosis in LAD and implanted stent in proximal-mid LAD. Therapy prescribed was providing antiplatelet and anticoagulation.Discussion: Acute Myocardial Infarction (AMI) and Acute Infarct Stroke (AIS) have a narrow therapeutic time-window and a delayed intervention may results in morbidity and death. Antiplatelet and anticoagulant used in PCI for AMI increase the risk for hemorrhagic, and AIS with thrombolytic increase the risk of cardiac wall rupture in AMI. Direct Oral Anticoagulant (DOAC) treatment should reduce ischaemia and lower bleeding. The optimal time point to start anticoagulant treatment might be between 4-14 days after the onset of stroke. Duration of post-PCI triple therapy should be minimized depending on bleeding and risks of ischemia.